Assessment of Digital Integration in Learning - Khatiwada, Shreeraj (International Research Journal of MMC, 2024)
This research explores the integration of digital tools, particularly mobile learning, in educational contexts in Nepal, aiming to optimize their effectiveness. Employing a questionnaire-based methodology, data was collected from students across all over Nepal using a Google Form distributed through online media. Insights were gathered from 1104 students, revealing widespread ownership and usage of mobile devices for studying. Findings indicate a preference for laptops and smartphones, with web pages and applications being the most utilized resources. Significant associations were observed between the type of mobile device, academic major, and preference for mobile learning. The study concludes that digital tools play a critical role in modern education, emphasizing the need for comprehensive policies to promote their integration. Recommendations include government initiatives to enhance access to educational devices, conduct proper trainings to learners, expand internet connectivity, address technical challenges, and distribute digital equipment to enhance mobile learning experiences for equity of access to technology all over Nepal.